2011
DOI: 10.1007/s13258-010-0114-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of reference genes for normalization of gene expression in thoroughbred and Jeju native horse(Jeju pony) tissues

Abstract: Quantitative analysis of horse gene expression profiles under diverse experimental conditions is limited by the lack of reliable reference genes for normalization of mRNA levels. Therefore, in this study, the expression of potential reference genes was compared between thoroughbred and Jeju native horse (Jeju pony). We compared the expression of nine genes by quantitative real-time RT-PCR in fourteen tissues between the two horse breeds and analyzed their stability using the geNorm and NormFinder programs. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…According to the Minimum Information for Publication of Quantitative Real-Time PCR Experiments (MIQE) guidelines, reference genes are now selected based on their specificity in interactions between a species or tissue subjected to different experimental treatments. Several studies have reported evaluations of reference gene in animals such as cattle [ 5 ], pig [ 6 ], sheep [ 7 ], goat [ 8 ], horse [ 9 ], fish [ 10 ], and birds [ 11 ]. However, a limited number of studies have investigated identification of reference genes used in chicken ( Gallus gallus ).…”
Section: Introductionmentioning
confidence: 99%
“…According to the Minimum Information for Publication of Quantitative Real-Time PCR Experiments (MIQE) guidelines, reference genes are now selected based on their specificity in interactions between a species or tissue subjected to different experimental treatments. Several studies have reported evaluations of reference gene in animals such as cattle [ 5 ], pig [ 6 ], sheep [ 7 ], goat [ 8 ], horse [ 9 ], fish [ 10 ], and birds [ 11 ]. However, a limited number of studies have investigated identification of reference genes used in chicken ( Gallus gallus ).…”
Section: Introductionmentioning
confidence: 99%
“…For comparison four traditional RGs, two universal RGs and one expressed repetitive element were selected. The traditional RGs were selected just by educated guess-work and tradition ( ACTB and GAPDH , [ 30 ]) or based on stable expression across a panel of equine tissues ( UBB and B2M , [ 31 , 32 ]). The universal RGs, OAZ1 and RPS29 , exhibited highly uniform expression in men and mice across a plenitude of conditions [ 33 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…The melting curves were determined by increasing the temperature from 55°C to 99°C over a period of 30 s. All samples were amplified in triplicate to ensure reproducibility. As a standard control, the UBB gene was amplified with the primer pair described by Ahn et al (2011).…”
Section: Quantitative Rt-pcr Analysismentioning
confidence: 99%